2020
DOI: 10.2147/ccid.s247171
|View full text |Cite
|
Sign up to set email alerts
|

<p>Delayed Inflammatory Reactions to Hyaluronic Acid Fillers: A Literature Review and Proposed Treatment Algorithm</p>

Abstract: Background and Objectives: There is a wide diversity of opinions regarding the management of delayed inflammatory reactions (DIRs) secondary to hyaluronic acid (HA)-based fillers. The plethora of approaches has led the authors to conduct a review regarding management and treatment of DIRs as well as establish therapeutic guidelines for this purpose. Materials and Methods: A review of the literature was performed through databases such as PubMed using keywords including HA-fillers and complications, delayed HA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
92
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 28 publications
0
92
0
Order By: Relevance
“…In the 400 subjects studied retrospectively, the authors did not report a DIR related to post viral illness or vaccination [21]. However, several studies have shown that the biphasic highlycrosslinked Juvederm vycross filler product line has a higher than expected rate of DIR [3,5,22]. It is has been reported Fig.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In the 400 subjects studied retrospectively, the authors did not report a DIR related to post viral illness or vaccination [21]. However, several studies have shown that the biphasic highlycrosslinked Juvederm vycross filler product line has a higher than expected rate of DIR [3,5,22]. It is has been reported Fig.…”
Section: Discussionmentioning
confidence: 95%
“…A recent expert consensus panel defined the duration of DIRs as arising from a normal state 2-4 weeks or longer post-injection [5]. Clinically, they noted that DIRs in HAbased filler injections manifest as erythema, painful nodules, induration, and eyelid edema.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations